Emotional Loneliness in Elderly: Association with Cognitive Performance and Sleep Quality in One of Indonesia’s Rural Areas - Olga Atsira; Ayu Nisa'; Muhammad Hanun Mahyuddin; Rakha Rahmatullah; Aita Silia; Azimatul Karimah (Jurnal Psikiatri Surabaya)
Introduction: A growing body of studies focuses on the association between loneliness defined as social isolation with sleep quality and cognitive performance, whereas emotional loneliness has not received much attention.